tDCS randomized controlled trials in no-structural diseases: a quantitative review - Eugenia Gianni (Nature Portfolio, 2021)
Abstract The increasing number and quality of randomized controlled trials (RCTs) employing transcranial direct current stimulation (tDCS) denote the rising awareness of neuroscientific community about its electroceutical potential and opening to include these treatments in the framework of medical therapies under the indications of the international authorities. The purpose of this quantitative review is to estimate the recommendation strength applying the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) criteria and PICO (population, intervention, comparison, outcome) model values for effective tDCS treatments on no-structural diseases, and to provide an estimate of Sham effect for future RCTs. Applying GRADE evaluation pathway, we searched in literature the tDCS-based RCTs in psychophysical diseases displaying a major involvement of brain electrical activity imbalances. Three independent authors agreed on Class 1 RCTs (18 studies) and meta-analyses were carried out using a random-effects model for pathologies sub-selected based on PICO and systemic involvement criteria. The meta-analysis integrated with extensive evidence of negligible side effects and low-cost, easy-to-use procedures, indicated that tDCS treatments for depression and fatigue in Multiple Sclerosis ranked between moderately and highly recommendable. For these interventions we reported the PICO variables, with left vs. right dorsolateral prefrontal target for 30 min/10 days against depression and bilateral somatosensory vs occipital target for 15 min/5 days against MS fatigue. An across-diseases meta-analysis devoted to the Sham effect provided references for power analysis in future tDCS RCTs on these clinical conditions. High-quality indications support tDCS as a promising tool to build electroceutical treatments against diseases involving neurodynamics alterations.